Cellular, Molecular and Non-Pharmacological Therapeutic Advances for the Treatment of Parkinson's Disease: Separating Hope from Hype - Ghamgosha, Mehdi; Latifi, Ali M.; Meftahi, Gholam Hossein; Mohammadi, Alireza (Current Gene Therapy, 2018)
Parkinson's Disease (PD) is a frustrating condition characterized by motor and nonmotor deficits majorly caused by the loss of dopaminergic cells in the Substantia Nigra pars compacta (SNc) and destruction of the nigrostriatal pathway. Despite the very respectable advances in cutting-edge approaches for the treatment of PD, there exist numerous challenges that have incapacitated the definitive treatment of this disease. This review emphasized the development of various non-pharmaceutical therapeutic approaches and mainly highlighted the cutting-edge treatments for PD including gene- and stem cell-based therapies, targeted delivery of neurotrophic factors, and brain stimulation techniques such as Transcranial Magnetic Stimulation (TMS), transcranial Direct Current Stimulation (tDCS), and Deep Brain Stimulation (DBS). The review covered various gene therapy strategies including Adeno-Associated Virus-Glutamic Acid Decarboxylase (AAV-GAD), AAV–Aromatic L-Amino Acid Decarboxylase (AAV-AADC), Lenti-AADC/Tyrosine Hydroxylase/Guanosine Triphosphate- Cyclohydrolase I (Lenti-AADC/TH/GTP-CH1), AAV–Neurturin (AAV-NRTN), α-Synuclein silencing, and PRKN gene delivery. Also, the advantages, disadvantages, and the results of trials of these methods were discussed. Finally, reasons for the failure of PD treatment were described, with the hopes separated from hypes.
Keywords: α-Synuclein silencing